Etude de quelques problèmes aux limites avec des conditions non locales - Noura Massidi (My University, 2024)
In this work, we study parabolic and hyperbolic problems with non-local conditions. We show the existence and uniqueness of the solution, the demonstration is based on two a priori estimates and on the density of all the values of the operator generated by the problem studied, and we use the transform method of Laplace which consists of seeking the solution to the problem. ------------------------------------------------------------------------------------------ في هذه المذكرة، قمنا بدراسة مسائل القطع المكافئ والقطع الزائد مع شروط غير محلية. نبين وجود الحل ووحدانيته، حيث يعتمد البرهان على تقديرين مسبقين وعلى كثافة مجموعة قيم العوامل المتولدة عن المسألة المدروسة، ونستخدم طريقة تحويل لابلاس التي تنص على البحث عن الحل. ------------------------------------------------------------------------------------------ Dans ce mémoire, on étudie des problèmes paraboliques et hyperboliques avec des conditions non locales. On montre l.existence et l.unicité de la solution, la démonstration est basée sur deux estimations a priori et sur la densité de l.ensemble des valeurs de l.opérateur engendré par le problème étudié, et on utilise la méthode de transformée de Laplace qui consiste à chercher la solution du problème.